(untitled) (Physical Education, Health and Social Sciences, 2025)
The present study examines the impact of conflict resolution training on organizational justice perception and employee trust, with leadership fairness perception as a mediator and power dynamics and conflict resolution mechanisms (collaborative vs. avoidant) as moderators. Grounded in equity theory and social exchange theory, the research highlights how training enhances fairness and trust by promoting balanced relationships and reciprocal exchanges. The findings suggest leadership fairness mediates these effects, while collaborative mechanisms and balanced power dynamics strengthen positive outcomes. This study provides actionable insights for organizations to foster justice and trust through effective conflict resolution and leadership practices.